2010
DOI: 10.1002/fuce.200900126
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Nanocarbon‐Based Gas Diffusion Media by Electrochemical Impedance Spectroscopy

Abstract: A multi‐wall carbon nanotubes (MWCNTs)‐based gas diffusion medium (GDM) was prepared, where carbon black was partially substituted by carbon nanotube (CNT) in the formulation of the micro‐porous layer (MPL). A rheological analysis of the ink used to coat the gas diffusion layer (GDL) was previously performed to correlate viscosities with the slurry composition. Shear thinning inks with viscosity of 0.4 (Pa s–1) were obtained for a composition containing 10 wt.‐% of CNT and 12 wt.‐% of fluorinated polymer. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…At high humidity this behaviour is more evident, due to more pronounced mass transfer limitations. Indeed, the polarization resistance keeps constant or decreases somewhat at low current densities and this is usually ascribed to the lowering of the anode charge transfer resistance [38,40]; thus the increase of the sum Rp+Rd can be ascribed to diffusion resistance, which is more dramatic for CMC-containing MPLs due to hydrophilic feature of CMC. These trends can also explain the voltage drop observed in Figure 4 and Figure 5 at high cathodic RH, above all for CMC-PTFE12.…”
Section: Original Research Papermentioning
confidence: 98%
“…At high humidity this behaviour is more evident, due to more pronounced mass transfer limitations. Indeed, the polarization resistance keeps constant or decreases somewhat at low current densities and this is usually ascribed to the lowering of the anode charge transfer resistance [38,40]; thus the increase of the sum Rp+Rd can be ascribed to diffusion resistance, which is more dramatic for CMC-containing MPLs due to hydrophilic feature of CMC. These trends can also explain the voltage drop observed in Figure 4 and Figure 5 at high cathodic RH, above all for CMC-PTFE12.…”
Section: Original Research Papermentioning
confidence: 98%
“…On the basis of a previous work [50], carbon nanotubes (CNTs, Nanothinx NTX1, purity: 97%, diameter: 10e30 nm, length: 10 mm, metal particles: 3 wt %), partially replacing carbon black powder, were used in order to make final coatings more conductive than the standard one. Moreover, inks containing a hydrophobic agent other than PTFE (i.e.…”
Section: Preparationmentioning
confidence: 99%
“…A novel type of GDL prepared by growing carbon nanotubes directly on the fiber surface of carbon cloth was proposed in the work [4]. Stampino et al [5] fabricated a multi-wall CNTsbased MPL in which carbon black in the formulation of MPL was partially substituted by CNT. They assembled a single cell with the CNT-based MPL and found that its electrochemical performance was better than that obtained with a conventional MPL made by Vulcan XC-72R carbon black without any addition of CNT.…”
Section: Introductionmentioning
confidence: 99%